Does oseltamivir protect human chondrocyte and nucleus pulposus cells from degeneration by inhibiting senescence and proinflammation mediated by the NLRP3 inflammasome and NF-?B? - Yılmaz, İbrahim; Akalan, Hande; Öznam, Kadir; Karaarslan, Numan; Yaşar Şirin, Duygu; Özbek, Hanefi (Verduci Editore s.r.l, 2022)
OBJECTIVE: Recent drug design studies suggest that inflammation is among the most important factors in the development of both intervertebral disc (IVD) degeneration (IVDD) and osteoarthritis (OA) due to cartilage damage. This study aimed to investigate whether the anti-inflammatory drug oseltamivir has a toxic effect on IVD and cartilage tissue cells. It assessed what effect oseltamivir has on hypoxia-inducible factor (HIF)-1 alpha (HIF1?), which plays an important role in anabolic pathways in IVD and cartilage tissue. In addition, the study analyzed whether oseltamivir could inhibit the release of inflammatory interleukin-1 beta (IL-1?) via the nuclear factor kappa-B (NF-?B) signaling pathway by activating the nucleotide-binding oligomerization domain and leucine-rich repeat protein-3 (NLRP3) inflammasome. MATERIALS AND METHODS: Human lumbar IVD (n = 8) tissues were isolated for annulus fibrosus (AF) and nucleus pulposus (NP) primary cell cultures, and human tibial and femoral cartilage tissues (n = 8) were isolated for primary chondrocyte cultures. Untreated groups served as the control and oseltamivir-treated groups as the study sample. Cell viability and cytotoxicity were evaluated at 0, 24, 48, and 72 h in all groups for changes in HIF-1?, IL-1?, NF-?B, and the NLRP3-inflammasome protein expressions using Western blotting. The ? significance value was < 0.05. RESULTS: In the oseltamivir-treated groups, cell proliferation decreased in both AF/NP cell and chondrocyte cultures obtained from IVD cartilage tissues. After Western blotting analysis, changes were observed in the protein expressions of HIF-1?, IL-1?, NF-?B, and the NLRP3 inflammasome in both AF/NP cells and chondrocytes. The results were statistically significant (p < 0.05). CONCLUSIONS: Oseltamivir treatment may be a promising regenerative strategy to manage IVDD and osteoarthritic cartilage tissues.
Does oseltamivir protect human chondrocyte and nucleus pulposus cells from degeneration by inhibiting senescence and proinflammation mediated by the NLRP3 inflammasome and NF-kappa B?
Does oseltamivir protect human chondrocyte and nucleus pulposus cells from degeneration by inhibiting senescence and proinflammation mediated by the NLRP3 inflammasome and NF-kappa B?
Keywords: Degeneration; Inflammation; NF-?B; NLRP3 Inflammasome; Oseltamivir